2003
DOI: 10.1111/1469-8986.00107
|View full text |Cite
|
Sign up to set email alerts
|

To err is autonomic: Error‐related brain potentials, ANS activity, and post‐error compensatory behavior

Abstract: A two-component event-related brain potential consisting of an error-related negativity (ERN/Ne) and positivity (Pe) has been associated with response monitoring and error detection. Both the ERN and Pe have been source-localized to the anterior cingulate cortex (ACC)Fa frontal structure implicated in both cognitive and affective processing, as well as autonomic nervous system (ANS) modulation. The current study sought to examine the relationships among the ERN, the Pe, two autonomic measures, and behavior. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
469
12
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(536 citation statements)
references
References 51 publications
(71 reference statements)
54
469
12
1
Order By: Relevance
“…Although we do not have neuroimaging data from the BAT, it is based on the Go/NoGo format which has previously shown a relationship between post-error slowing and error-related ACC activity , replicating a relationship demonstrated with other cognitive tasks such as the flanker (Gehring et al, 1993) and Stroop tasks (Kerns et al, 2004(Kerns et al, , 2005. Despite this evidence some studies have failed to demonstrate a relationship between error-related ACC activity and post-error slowing (Gehring and Fencsik, 2001), or have associated different neural signatures with post-error slowing, such as the ERP error positivity (Pe) waveform (Hajcak et al, 2003). Studies examining the diminished error-related ACC response of older adults have also failed to show that it bears any relationship to posterror slowing (Themanson et al, 2005;West and Moore, 2005), and studies examining drug-related increases (Riba et al, 2005a;Tieges et al, 2004) or decreases (Easdon et al, 2005;Riba et al, 2005b) in the ACC response to errors have also failed to show a relationship to post-error slowing.…”
Section: Post-error Adaptationmentioning
confidence: 77%
“…Although we do not have neuroimaging data from the BAT, it is based on the Go/NoGo format which has previously shown a relationship between post-error slowing and error-related ACC activity , replicating a relationship demonstrated with other cognitive tasks such as the flanker (Gehring et al, 1993) and Stroop tasks (Kerns et al, 2004(Kerns et al, , 2005. Despite this evidence some studies have failed to demonstrate a relationship between error-related ACC activity and post-error slowing (Gehring and Fencsik, 2001), or have associated different neural signatures with post-error slowing, such as the ERP error positivity (Pe) waveform (Hajcak et al, 2003). Studies examining the diminished error-related ACC response of older adults have also failed to show that it bears any relationship to posterror slowing (Themanson et al, 2005;West and Moore, 2005), and studies examining drug-related increases (Riba et al, 2005a;Tieges et al, 2004) or decreases (Easdon et al, 2005;Riba et al, 2005b) in the ACC response to errors have also failed to show a relationship to post-error slowing.…”
Section: Post-error Adaptationmentioning
confidence: 77%
“…Post-error slowing. Trials after errors were used for the analysis of the error-related slowing (Gehring et al, 1993;Hajcak et al, 2003;Rabbit, 1981). During the task, in every condition each picture was presented twice as a go-trial, which allowed us to select button-press latencies for the same pictures for a post-error trial and a correct trial.…”
Section: Results-experimentsmentioning
confidence: 99%
“…A positive correlation between slowing after errors and performance on post-error trials was also expected. Hajcak et al (2003) found, for instance, that participants who showed more slowing after errors also exhibited a better performance on post-error trials.…”
Section: Current Studymentioning
confidence: 95%
“…There is some evidence that midfrontal negativities related to performance monitoring (ERN, FRN) are subject to emotional influences [28-32]. Luu and colleagues [31], for instance, could observe group differences in the ERN related to participants' trait anxiety.…”
Section: Discussionmentioning
confidence: 99%